2018
DOI: 10.1093/toxsci/kfy222
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Meconium Acetaminophen and Childhood Neurocognitive Development in GESTE, a Canadian Cohort Study

Abstract: Acetaminophen is the only over-the-counter pain reliever that is not contraindicated during pregnancy, but recent studies have questioned whether acetaminophen is safe for the fetus, particularly the developing brain. This prospective birth cohort study probed the previously observed association between in utero exposure to acetaminophen and neurodevelopment by using concentrations of acetaminophen measured in meconium, which more objectively captures exposure of the fetus than maternal report. Exposure, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Effect sizes were generally modest but because exposure is widespread 1,107 , even a small effect size could translate into a large number of affected children. Dose-response has been investigated in 19 studies [112][113][114][116][117][118][119][120][121][122]124,[127][128][129][130]133,[136][137][138] and of these, 16 studies 112,114,[116][117][118][119][120][121][122]124,127,129,130,133,136,137 identified a dose-response association, whereby increased duration of exposure was associated with increased risk. In many of these studies, associations were weak for short-term exposure suggesting that short-term use might be of limited risk.…”
Section: The Epidemiological Evidence Of Neurodevelopmental Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect sizes were generally modest but because exposure is widespread 1,107 , even a small effect size could translate into a large number of affected children. Dose-response has been investigated in 19 studies [112][113][114][116][117][118][119][120][121][122]124,[127][128][129][130]133,[136][137][138] and of these, 16 studies 112,114,[116][117][118][119][120][121][122]124,127,129,130,133,136,137 identified a dose-response association, whereby increased duration of exposure was associated with increased risk. In many of these studies, associations were weak for short-term exposure suggesting that short-term use might be of limited risk.…”
Section: The Epidemiological Evidence Of Neurodevelopmental Effectsmentioning
confidence: 99%
“…Using methods such as sibling control design, polygenic risk scores and negative controls, efforts were made to control genetic confounding in 16 studies with little effect on the reported associations in all but two of these studies 115,116 . APAP exposure assessment relied on maternal self-report in 24 studies, on biomarkers in five studies [127][128][129][130]137 and on prescription records in one study 138 . Although one study that used both biomarkers and self-reported exposure suggested that the two measures of exposure were correlated 127 , exposure misclassification remains a concern in studies using maternal self-report 24 .…”
Section: The Epidemiological Evidence Of Neurodevelopmental Effectsmentioning
confidence: 99%
“…Neonatal meconium collected after birth may actually be the best way to capture prolonged intrauterine exposure to paracetamol and other drugs, as it accumulates chemicals from the fetal bile and the fetal urine passed into the amniotic fluid which is ingested by the fetus. In the Canadian Gestation and the Environment Cohort, paracetamol in meconium was unrelated to the children's intelligence examined at 6-8 years of age [64] but showed a dose-response association with physician-diagnosed ADHD [62]. Each doubling of exposure increased the odds of ADHD by 10% among 345 children analyzed, 199 (57.7%) of whom had detectable paracetamol in meconium, and 33 (9.6%) were diagnosed with ADHD.…”
Section: Paracetamol Use During Pregnancymentioning
confidence: 98%
“…We conducted analyses using data from the prospective GESTE cohort, which is described in detail elsewhere [34,35,69,70]. In short, GESTE cohort is comprised of (a) women residing in the Eastern Townships (Estrie) of Quebec, Canada having a pregnancy between 2007 and 2009 and (b) children born from these pregnancies.…”
Section: Participantsmentioning
confidence: 99%